Process Intensification of Low-Temperature Syngas Production via the LT-rWGS: A Fluidized-Bed Reactor with Continuous Sorbent Feeding (CSF) - González Pizarro, Rodrigo; Lasobras Laguna, Javier; Renda, Simona; Soler Herrero, Jaime; Menéndez, Miguel; Herguido, Javier (Jornada de Jóvenes Investigadores del I3A, 2025)
This study explores the process-intensification of green carbon-monoxide (CO) synthesis —an essential building block for the petrochemical sector and a promising vector for the energy transition— using a sorption-enhanced fluidized-bed reactor (SEFBR) continuously supplied with fresh sorbent (CSF).